SAT0384 Evolving patterns of reactive arthritis. (12th June 2018) - Hayes, K.M.; Hayes, R.; Pope, J.
Abstract : Background: Reactive arthritis (ReA) seen by rheumatologists may be changing in frequency (less common) and severity (less than full triad of symptoms and less chronic ReA). Epidemiologic changes in ReA could be due to less food borne illness, cleaner water, and possibly more rapid treatment of sexually transmitted diseases or for other unknown reasons. Objectives: To understand rheumatologists' perspectives about changes in frequency, severity, and manifestations of ReA. Methods: After obtaining ethics approval, 548 members of the Canadian Rheumatology Association (CRA) were surveyed via email with a reminder email. There were 6 groups of questions: demographic information, views from respondents regarding the prevalence of ReA (including acute, recurrent, and chronic), tests ordered to investigate suspected ReA, treatments prescribed for ReA, causes of ReA in their practices, and perspectives on changes in the incidence, severity and causes of ReA over time. Descriptive statistics were used to analyse the data. Results were by physician report and were not confirmed by chart audits. Results: Sixty-six rheumatologists completed the survey (15.5% response rate). The results of the survey indicated that 47% of rheumatologists believed that the incidence of ReA is declining, compared to 6% who thought it was increasing; and that the common causes may be changing (39% agreed/strongly agreed with a mean 3.4/5 on the Likert scale). Acute, chronic, and recurrent ReA were all perceived to have similar frequencies in their practices. In terms of presentation, asymmetric oligoarthritis occurred in the majority of ReA seen by those surveyed (78%). Full triad ReA (arthritis, conjunctivitis, urethrits) was thought to occur in 21% of ReA cases, and patients with conjunctivitis were very likely to exhibit the rest of the triad. Similarly, patients with recurrent ReA were more likely to exhibit the full triad (43%) compared to acute or chronic ReA (14%). Rheumatologists believed that the infectious cause of ReA was found in only 35% of cases. The data indicate that the most common cause of ReA was 'unknown' infectious organisms, followed by gastrointestinal (GI) infections and sexually transmitted infections (STIs). Multiple tests were ordered to investigate ReA. The three most common investigations ordered by respondents included testing for chlamydia (66%), C-reactive protein (CRP) (62%), and human leukocyte antigen (HLA-B27) (50%). Imaging was ordered by 39% of respondents with sacroiliac (SI) joint imaging ordered by 21%, X-rays of the affected joints by 15%, and other imaging by 7.5%. Figure 1 shows these results. Treatments used for ReA varied, as shown in figure 2. The most common treatments for ReA were nonsteroidal anti-inflammatory drugs (NSAIDS) (97% frequently or always used), intra-articular corticosteroid injections (65% frequently or always used), and disease-modifying antirheumatic drugs (DMARDs) (45% frequently or always used). Sixty-six percent said they used tumour necrosis factor alpha inhibitors (TNFi) at least occasionally in chronic ReA. Conclusions: Respondents tended to believe that ReA may be decreasing and the causes may be changing. In most cases the causative organism was thought to be unknown followed by GI and STIs. Interestingly, full triad ReA was thought to be linked with recurrent ReA. The results suggest several avenues for exploring clinical and epidemiological relationships in ReA. Disclosure of Interest: None declared